The Application of Money Market and Capital Market in Islamic Economic Perspective - Fitra Amar Rosuli; M. Aidil Syahputra; Yabib Fikri Rambe; Maryam Batubara (Sean Institute, 2025)
The money market is a place for short-term financial instrument transactions that function to meet the liquidity needs of economic actors, while the capital market provides long-term instruments such as stocks and bonds that support investment and sustainable economic growth. In Islamic economics, the presence of the money market and sharia capital market provides investment alternatives that are in accordance with sharia principles, avoiding elements of usury, gharar, and maysir, and emphasizing justice and transparency. This article also reviews the differences in characteristics, mechanisms, and instruments between conventional and sharia markets, and highlights the importance of implementing the principles of fiqh muamalah in the development of sharia financial markets in Indonesia. This study uses a literature study method by examining various relevant sources to deepen the study of the money market and capital market from an Islamic economic perspective, so that it can provide understanding and references for the development of sharia finance in the future.